Evaluation of Alcohol Preference and Drinking in msP Rats Bearing a Crhr1 Promoter Polymorphism - Logrip, Marian L.; Walker, John R.; Ayanwuyi, Lydia O.; Sabino, Valentina; Ciccocioppo, Roberto; Koob, George F.; Zorrilla, Eric P. (Frontiers in Psychiatry, 2018)
Alcoholism is a pervasive societal problem, yet available pharmacotherapies fail to treat most sufferers. The type 1 corticotropin-releasing factor receptor (CRF1) has received much attention for its putative role in the progression to alcohol dependence, although at present its success in clinical trials has been limited. Two single nucleotide polymorphisms in the rat Crhr1 promoter have been identified in the Marchigian sub-strain of Sardinian alcohol-preferring (msP) rats. Unlike other Wistar-derived alcohol-preferring lines, nondependent msP rats reduce their alcohol self-administration in response to CRF1 antagonists and show increased brain CRF1 expression. The current study tested the hypotheses that the A alleles in the Crhr1 promoter polymorphisms are: 1) unique to msP (vs. CRF1 antagonist-insensitive) alcohol-preferring lines, and 2) associate with greater alcohol preference or intake. Two related polymorphisms were observed in which both loci on a given chromosome were either mutant variant (A) or wildtype (G) alleles within the distal Crhr1 promoter of 17/25 msP rats (68%), as compared to 0/23 Indiana P rats, 0/20 Sardinian alcohol-preferring rats bred at Scripps (Scr:sP) and 0/22 outbred Wistar rats. Alcohol consumption in msP rats did not differ according to the presence of Crhr1 A alleles, but greater alcohol preference (98%) was observed in A allele homozygous msP rats (AA) compared to msP rats with wild-type (GG, 91%) or heterozygous (GA, 91%) genotypes. The greater alcohol preference reflected decreased water intake, accompanied by reduced total calories consumed by AA rats. The data show that msP rats differentially possess mutant A variant alleles in the polymorphic promoter region of the Crhr1 gene that may differentially regulate consumption.